An integrated approach to data confidentiality in 5G/6G based on LDPC codes and post-quantum cryptography - Dunaiev, Sergii (Національний технічний університет "Харківський політехнічний інститут", 2025)
Purpose of the research. Development and justification of an integrated data secrecy model that provides an optimal combination of coding and cryptography mechanisms to increase the level of security and efficiency of information processing in high-speed 5G/6G networks. The following results were obtained. A comprehensive analysis of authentication and coding methods in 5G and 6G networks was conducted. A comparative table of authentication and coding mechanisms, including post-quantum cryptographic algorithms (PQC), was developed. The advantages and limitations of existing 5G authentication methods were identified and the integration of PQC was proposed to improve security in 6G networks. The principles of LDPC codes were analyzed and their effectiveness in improving data confidentiality was demonstrated. An integrated data hiding model was proposed that combines LDPC coding with post-quantum cryptography to ensure both high-speed communication and resistance to quantum attacks. The presented models allow formalizing the processes of authentication, data transmission, and increasing confidentiality in next-generation networks, as well as their real-time adaptation to various network conditions and threat levels. Мета дослідження. Розробка та обґрунтування інтегрованої моделі прихованості даних, яка забезпечує оптимальне поєднання кодувальних і криптографічних механізмів для підвищення рівня безпеки та ефективності обробки інформації у високошвидкісних мережах 5G/6G. Отримано наступні результати. Проведено комплексний аналіз методів автентифікації та кодування в мережах 5G та 6G. Розроблено порівняльну таблицю механізмів автентифікації та кодування, включаючи постквантові криптографічні алгоритми (PQC). Визначено переваги та обмеження існуючих методів автентифікації 5G та запропоновано інтеграцію PQC для підвищення безпеки в мережах 6G. Проаналізовано принципи LDPC-кодів та продемонстровано їх ефективність у підвищенні конфіденційності даних. Запропоновано інтегровану модель приховування даних, яка поєднує LDPC-кодування з постквантовою криптографією для забезпечення як високошвидкісного зв'язку, так і стійкості до квантових атак. Представлені моделі дозволяють формалізувати процеси автентифікації, передачі даних та підвищення конфіденційності в мережах наступного покоління, а також їх адаптацію в режимі реального часу до різних мережевих умов та рівнів загроз.
Інтегрований підхід до прихованості даних у 5G/6G на основі LDPC-кодів та постквантової криптографії
Keywords: post-quantum cryptography; data secrecy; information protection; integrated model; quantum attacks; постквантова криптографія; прихованість даних; захист інформації; квантові атаки; LDPC-коди